Electrochemical behavior of cocaine cutting agents at the polarized liquid-liquid interface. (10th January 2022) - Borgul, Paulina; Sobczak, Karolina; Rudnicki, Konrad; Glazer, Piotr; Pawlak, Patrycja; Trynda, Anna; Skrzypek, Sławomira; Poltorak, Lukasz
Highlights: Majority of cocaine cutting agents are inactive at the ITIES. Molecular partitioning is followed using cyclic voltammetry. Ion partition diagrams are plotted for interfacially active cutting agents. The signal from amine based drugs is governed by their hydrophobicity. Abstract: In this work, we have used cyclic voltammetry to investigate the interfacial behavior of cocaine cutting agents at the electrified liquid-liquid interface formed between a solution of the water and 1, 2-dichloroethane phases. Among 27 chemical species used to adulterate cocaine street samples, only 8 were detectable in the available potential window. These include procaine, lidocaine, levamisole, hydroxyzine, caffeine, phenylethylamine, diltiazem, and diphenhydramine. From the calibration curves obtained using voltammetric data, we have extracted the electroanalytical parameters such as detection sensitivities, limits of detection, and limits of quantifications. Also, for each electrochemically active drug, we have calculated diffusion coefficients and plotted the ion partition and concentration fraction diagrams. All this information is discussed in a view of the cocaine sensors development focused on its detection from demanding matrix defined by the street samples composition. Graphical Abstract: Image, graphical abstract